2011
DOI: 10.1002/ca.21119
|View full text |Cite
|
Sign up to set email alerts
|

Use of MRI images to measure tissue thickness over the ischial tuberosity at different hip flexion

Abstract: The goal of this experiment was to investigate changes in the thickness of the soft tissue overlying the ischial tuberosity (IT) due to changes in hip flexion angle and the addition of a sitting load. Eleven healthy subjects were tested. An apparatus constructed from foam blocks and an air bladder was used to position the subjects in different postures within an MRI tube. MRI images of the buttocks and thigh were obtained for four postures: Supine, 45° Hip Flexion, Non-Weight-Bearing 90° Hip-Flexion, and Weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…Specifically, Makhsous et al (2011) found that nonweight-bearing hip flexion decreased the thickness of the tissues overlying the ischial tuberosity by up to 44.1% relative to a supine position. Interestingly, though, our findings contrast with several reports that soft tissue thickness in the pelvic region increases as muscle activation increases (Hodges et al, 2003;Makhsous et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Specifically, Makhsous et al (2011) found that nonweight-bearing hip flexion decreased the thickness of the tissues overlying the ischial tuberosity by up to 44.1% relative to a supine position. Interestingly, though, our findings contrast with several reports that soft tissue thickness in the pelvic region increases as muscle activation increases (Hodges et al, 2003;Makhsous et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…, respectively, than in the supine position (Makhsous et al, 2011). Additionally, ultrasonography has been used to demonstrate that muscle thickness (across the tibialis anterior, biceps brachii, brachialis, transversus abdominis, obliquus internus abdominis, and obliquus externus abdominus) increases with activation level (Hodges et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that this was likely because the skin is the thinnest of the three layers. 8 It is known that high-frequency sonography can visualize tiny measurements like skin thickness that simply cannot be shown by standard MRI scans. 23 High-resolution ultrasound also has great advantages for the diagnostic evaluation of deep tissue injury.…”
Section: Neurologic Levels Nmentioning
confidence: 99%
“…7 Recent studies using MR images have examined deep tissue deformations and physiological characteristics of the skin, subcutaneous fat and muscle in weight-bearing and supine positions. 8,9 However, there have been no controlled studies comparing differences in skin thickness over bony prominences between patients with SCI and control subjects using ultrasonographic measurements. The aim of this study was to evaluate the differences in the thickness of the skin overlying the greater trochanter, ischial tuberosity, and sacrum between individuals with SCI and volunteers without SCI.…”
Section: Introductionmentioning
confidence: 99%